Business Communication Techniques for Lawyers - Ilieva-Koleva, Daniela (Wydawnictwo C.H. Beck, 2017)
The dynamic business environment and the changes in the perception of and sensitivity to time, affect also the business communication skills needed for the successful business people. Nowadays, particular trends exist in how business people communicate and these become applicable to corporate lawyers and to the law industry as well. One of the trends is that successful communication in business is the communication in which people are left with positive feelings after communicating with one another. The article aims to use as grounds Mehrabian’s communication research and to provide time-sensitive improvement possibilities through neuro-linguistic programing techniques and coaching tools for verbal and non-verbal communication. These are valid and proven to be effective in the corporate law sector as well. The article’s limitations come from the fact that it creates a general discussion on business communication for lawyers without going into the specifics of the law profession and the variety of manifestations.
Keywords: business communication for lawyers; NLP in business communication; coaching for lawyers; law practice communication